Sprawl and mega-events: Economic growth and recent urban expansion in a city losing its competitive edge (Athens, Greece) - Luca Salvati; Marco Zitti (Urbani Izziv, 2017)
In the new context of contemporary cities, local competitiveness for financial resources has grown more than ever, resulting in cities characterised by important socioeconomic transformations. Earlier studies addressed the relation between urban expansion, socioeconomic development and mega-events only for specific areas and types of urban growth, often overlooking the role of mega-events in fuelling urban sprawl. As the host of the 2004 Olympic Games, Athens, Greece is a paradigmatic example for emerging cities hosting mega-events due to the close interconnection between the Olympics, infrastructure development and urban sprawl. This article connects the latent relationship between economic expansion driven by the Olympic Games and laissez-faire urbanism to the long-term unregulated urban expansion characterising Athens’s development. By providing room for the original wave of sprawl, the resulting socioeconomic context is interpreted as a signal of the weakness of the “competitive city” framework in poorly planned and long-deregulated urban contexts such as Athens. A comprehensive analysis of recent phases of economic growth and discontinuous urban expansion thus provides further insight into understanding sprawl processes in today’s cities, and helps distinguish the morphological patterns and socioeconomic dynamics that characterise urban expansion during sequential cycles of economic expansion and recession.